MATHEMATICS IN TEACHING OF THE MATTER ESSENCE - S.T.Qasimova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Mathematics science in teaching issues solve very important place holds , because the problem is solved target-students theoretical knowledge every character practical issues solve in the field conscious respectively fast and persistence with application to do is to teach . Problem solving is mathematical theory in practice application from doing consists of Mathematics solving problems in teaching pedagogical essence how much big the fact that and teacher own work both in planning and teaching at the same time How attention to give need that’s it better than said is understood .